Religion, Colonization and Decolonization in Congo, 1885-1960. Religion, colonisation et décolonisation au Congo, 1885-1960 - De Maeyer, Jan, 1952-; Cleys, Bram; Viaene, Vincent, 1967- (Book collections on Project MUSE., 2020)
The contributions in this book provide insight into the multifaceted history of the interaction between religion and colonization.